Comparing International and American Students’ Challenges: A Literature Review - Perry, Cody J. (Journal of International Students, 2016)
International student numbers have increased drastically in the past few years. International students provide benefits to universities and American students such as greater revenue, and more open-mindedness. There have been myriad studies that have examined the international student experience, but most have focused solely on international students. However, a careful examination of the current literature demonstrates that the presence of international students in the United States offers a variety of benefits to American students by improving cultural awareness, students’ self-evaluated skills, and even the American economy. This literature review highlights future research that should be performed as well as strategies that can be implemented by faculty and administration to help international students who are currently studying in the United States.